THE “AB AURO” PROLOGUE OF PELBARTUS OF THEMESWAR’S THEOLOGICAL ENCYCLOPEDIA - Alexandra BANEU (Studia Universitatis Babeș-Bolyai. Philosophia)
The Ab Auro Prologue of Pelbartus of Themeswar’s Theological Encyclopedia. Pelbartus of Themeswar is a 15th century observant Franciscan best known for his collections of model sermons. This article, however, treats one of the two prologues which accompany his work of systematic theology, the Aureum sacrae theologiae rosarium. The Ab auro prologue, which is discussed in detail in the present study, introduces the reader to the main intent of the work. It has a rich metaphoric style and is tacitly inspired by the “Primum principium” of William of Vaurouillon’s commentary on the Sentences of Peter Lombard.